Indopamphantus makutaensis, a new genus and species, and Indopamphantini, a new tribe of Pamphantinae (Hemiptera: Heteroptera: Geocoridae), as the first representative of the subfamily from the Oriental Region - Malipatil, M. B. (Zootaxa, 2017)
Indopamphantini trib. nov., a new tribe of subfamily Pamphantinae of family Geocoridae, is erected for Indopamphantus gen. nov., containing one species, I. makutaensis sp. nov., as the first member of this subfamily from the Oriental Region. The strikingly myrmecomorphic I. makutaensis, collected only from Makuta range area within Coorg [Kodagu] district at altitudes of up to 909 metres in the canopy of Vateria indica L. (Dipterocarpaceae), a tree indigenous to the Western Ghats in south India, is described and illustrated. The affinities of the new tribe with other tribes within the Pamphantinae as well with other related subfamilies of Geocoridae and families of Lygaeoidea are discussed. The Geocoridae and Pamphantinae are redefined to accommodate this new tribe.